WORK FROM HOME- A SUCCESS OR FAILURE IN DEVELOPING COUNTRY LIKE INDIA - Goel, Shweta; Monika (International Journal of Research -GRANTHAALAYAH, 2016)
Work carried out by an individual in his or her home or any other place of his/her choice is called work from home. This paper presents an overview of work from home concept and explains its necessity in today’s time. This paper focus on recent status of WFH in India and challenges faced by it in its implementation.